Incorporation of polysaccharide nanowhiskers into a poly(ethylene-co-vinyl alcohol) matrix - Du Toit, Madeleine Leonore (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.